Sickle Cell Crisis and the Acute Abdomen - Nazem, Ahmad (1986)
Abdominal pain is one of the most common symptoms in sickle cell crisis, and its cause remains controversial. Simple vaso-occlusive crisis may be an explanation. The abdominal pain may also reflect an acute surgical abdomen. A patient presented with sickle cell crisis and abdominal pain; he had a periappendiceal abscess at the site of an appendiceal stump five months after appendectomy. The role of sickle cell anemia in the pathogenesis of this abscess is uncertain.